Monitoring of offshore platform subsidence using permanent GPS stations - Setan, Halim; Othman, Rusli (2005)
Offshore platforms undergo subsidence,especially due to production activities. The monitoring of such subsidence requires specialised technique (i.e. GPS) as the platforms are situated at sea (i.e. hundreds of kms from mainland). Unfortunately standard GPS processing procedure is unable to achieve the required accuracy (several cm) over long baselines. The research focuses on the development of processing strategy (i.e. estimation and subsidence analysis) for monitoring of offshore platform subsidence using three permanent GPS stations of the Malaysia Active GPS system (MASS). The estimation of each epoch employs Bernese GPS software, followed by subsidence analysis using in-house software. Preliminary results are also shown.